Affective Reflection and Its Impact on Student Performance: Insights from the 1st Student Annual Seminar - Maulina (Jurnal Genesis Indonesia, 2024)
This study investigates how affective reflection affects students' performance when they present their papers at the first student annual seminar. Students who intentionally reflected on their feelings before, during, and following academic presentations engage in affective reflection. Using a qualitative methodology, the study used reflective journals to gather data from 20 student participants. The findings demonstrate that worry and the fear of making a mistake typically govern pre-presentation thinking, which either boosts or deflates students' self-esteem. Students' real-time emotional reactions, such as anxiety or enthusiasm, affect how they interact with the audience and present their material during the presentation. Reflections after a presentation show a significant relationship between emotional release and the capacity to evaluate one's performance objectively, pinpoint strengths, and pinpoint areas in need of development. Besides, encouraging affective reflection as a component of academic preparation can significantly improve student performance by elevating emotional consciousness and self-control.